Myocardial rupture after acute myocardial infarction. Ten year review. - Feneley, M P (1983)
Forty-nine patients with myocardial rupture complicating acute myocardial infarction were managed in our coronary care unit from 1972 to 1981: 33 patients with post-infarction ventricular septal defect, 12 patients with isolated rupture of the free wall of the left ventricle, and four patients with papillary muscle rupture. Nine of 19 patients (47%) who underwent surgical repair of a post-infarction ventricular septal defect survived. The major determinant of survival was the preoperative haemodynamic status. Ten of 13 patients (77%) who developed cardiogenic shock preoperatively died, while none of the six patients who were not in cardiogenic shock died. Survival was not related to the site or size of infarction, extent of coronary artery disease, or magnitude of the left to right shunt. There were no survivors among the 14 patients with post-infarction ventricular septal defect managed without surgical intervention. Seven of the 12 patients with isolated rupture of the free wall of the left ventricle developed mechanical cardiac arrest and died at the onset of rupture, but five patients developed subacute heart rupture and two of these patients survived after urgent surgical repair. Two of the four patients with papillary muscle rupture underwent mitral valve replacement, but both died in the early postoperative period; both patients who were not operated on died. Early detection and early surgical intervention are essential in the management of myocardial rupture complicating acute myocardial infarction.